Long filamentous state of Listeria monocytogenes induced by sublethal sodium chloride stress poses risk of rapid increase in colony-forming units. (June 2021) - Yamaki, Shogo; Kawai, Yuji; Yamazaki, Koji
Abstract: Bacterial cell filamentation is induced in response to sublethal stress in Listeria monocytogenes. The formation of filamentous cells, which have plural nucleoids and are connected in rows, is thought to result in the underestimation of viable cell counting using the agar plating method. Filamentous cells are able to return to their initial normal-sized morphology under stress-free conditions. However, the differences in the growth behavior of filamentous cells remain poorly understood. In this study, we established a long filamentous population induced by sublethal sodium chloride stress and compared the growth characteristics of normal-sized cells and filamentous cells in a stress-free environment. Sodium chloride (NaCl) (10%) was selected as the sublethal stress for L. monocytogenes IID 579 filamentation, subsequently inducing high levels of filamentation in L. monocytogenes IID 579. Fluorescent microscopy showed that single filamentous cells have multi nucleoids with or without membrane septa, while time-lapse imaging revealed that the formation of membrane septa and cell division of filamentous cells occurred simultaneously at multiple sites, unlike in normal-sized cells. The viable cell count of filamentous L. monocytogenes increased faster than that of normal-sized cells only in the early exponential phase, caused by reverting to the normal morphology from the filamentous state. Moreover, in the limited nutrient media in which normal cells did not proliferate, the colony-forming units of filamentous cells increased rapidly depending with a decrease in the filamentous cell rates. The thermal resistance of filamentous cells induced by NaCl was found to increase, suggesting that stress adaptation protects filamentous L. monocytogenes from various food-related stresses. These findings demonstrate that filamentous cells may have a higher stress tolerance than non-stressed cells, with a risk of a rapid increase in colony-forming units after the release of stress factors. The contamination by filamentous cells should be avoided, which will require conditions suitable for the prevention of filamentation in food safety. Highlights: Sublethal NaCl stress induced high level of filamentation in L. monocytogenes. Cell division occurred simultaneously at multiple sites in single filamentous cells. CFUs of filamentous L. monocytogenes increased faster than that of normal cells.